Study on toxicity and bioavailability of metals from urban PM2.5 and PM10 extracted in simulated biological fluids: in vitro and in vivo assessment - Juri Rimauro; Gaetana Napolitano; Gianluca Fasciolo; Paola Venditti; Angelo Riccio; Elena Chianese (Ecotoxicology and Environmental Safety, 2025)
Airborne particulate matter (PM), particularly fine (PM2.5) and coarse (PM10) fractions, contains toxic metals that contribute to oxidative stress development and adverse health effects. This study evaluates the bioavailability and toxicity of both regulated metals (Pb, Cd, Ni, As) and unregulated metals (Fe, Cu, Zn, V) in urban PM using simulated biological fluids (SBFs) to replicate different human exposure routes. The metal solubility was assessed using Gamble’s solution (neutral lung interstitial fluid), artificial lysosomal fluid (ALF), artificial saliva, and artificial tear fluid, simulating inhalation, ingestion, and ocular contact, respectively. Results indicate that acidic fluids (ALF) significantly increased the solubility of Cu, Pb, and Fe, particularly in PM2.5, due to enhanced proton-driven metal leaching. PM2.5 extracts consistently exhibited higher bioavailable metal concentrations than PM10, reflecting the greater surface area and reactivity of fine particles. Toxicological evaluations using the Artemia franciscana model revealed that PM exposure alters redox homeostasis by increasing reactive oxygen species (ROS) content, lipid peroxidation, and protein carbonylation and inducing the increase in antioxidant activity of the enzymes glutathione peroxidase and reductase. PM2.5 extracts had a greater toxic impact, suggesting a stronger link between fine particulate-bound metals and oxidative damage. By standardizing SBFs and integrating information obtained through chemical and biological approaches we get more information on the bioavailability and potential harmful effects of metals associated with PM. The findings highlight the need for more stringent air quality controls, mainly targeting PM2.5 due to its increased metal bioavailability and toxicity. Furthermore, this study validates Artemia franciscana as a cost-effective and ethically acceptable model for in vivo toxicological assessments.